PENERAPAN EVIDENCE BASED NURSING DENGAN INTERVENSI ORAL HYGIENE MENGGUNAKAN CHLORHEXIDINE DALAM MEMINIMALKAN RISIKO VENTILATOR ASSOCIATED PNEUMONIA (VAP) PADA PASIEN TERPASANG VENTILASI MEKANIK DI INTENSIVE CARE UNIT (ICU) - Tiyas Putri Widjayanti (2022)
Mechanical ventilation is a breathing apparatus that is used to maintain ventilation and provide oxygen for a long period. Mechanical ventilation is required by patients undergoing treatment in the Intensive Care Unit (ICU) room with indications of decreased consciousness or awareness of experiencing limitations in physical mobility and requiring a breathing apparatus. Mechanical ventilation installed in patients for a long time can mediate the entry of bacteria directly into the respiratory system and cause increased production of secretions so that it becomes a breeding ground for bacteria and causes Ventilator-Associated Pneumonia (VAP). Ventilator-Associated Pneumonia (VAP) is a nosocomial infection that causes respiratory problems in patients in the form of pneumonia after 48 hours or more the patient is assisted to breathe using mechanical ventilation in the ICU. The incidence of VAP can be reduced by nursing interventions, one of which is by consistently performing oral hygiene using chlorhexidine. The purpose of this innovative intervention is to reduce microbial colonization in the oropharynx and reduce the incidence of VAP in intubated patients in the ICU. After the innovation intervention was carried out for 3 days where oral hygiene was carried out twice a day, namely at 8-9 in the morning and 16-17 in the afternoon. Then, the managed patients and the resumed patients who were mechanically ventilated were evaluated using the CPIS score with a CPIS score of <6 so that the two patients who were given oral hygiene using 0.2% chlorhexidine did not show signs of VAP infection. This proves that oral hygiene using chlorhexidine which is carried out routinely by standard operating procedures is effective in reducing the incidence of VAP.